MOLECULAR EXCLUSION CHROMATOGRAPHY OF CRUDE VENOM AS AN AUXILIARY TOOL TO IDENTIFY HYBRID HONEYBEE POPULATIONS - Palma, M.s. [UNESP]; Brochetto-braga, M.r. [UNESP]; Chaud-netto, J. [UNESP]; Malaspina, O. [UNESP]; Oliveira, M.r. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 1995)
A comparison among the profiles of molecular exclusion chromatography in Sephadex G 100 column of venoms from Apis mellifera adansonii and Africanized honeybees revealed unique peaks which might be used to identify these populations. The venoms from hybrid populations resulting from the reciprocal mating of Apis mellifera adansonii and Africanized honeybees presented unique peaks, probably resulting from a synergistic effect between the parental genomes. The occurrence of characteristic peaks in venoms of hybrid populations might be used to identify these populations as well as to distinguish them from their parents.
Keywords: Apis mellifera; venom; hybrid populations; molecular exclusion chromatography; honeybees